Pengaruh Brand Image dan Brand Awareness terhadap Keputusan Pembelian Produk Air Minuman Dalam Kemasan (AMDK) AQUA: Studi Kasus pada Masyarakat Kecamatan Sukajadi Kota Bandung - Rini Handayani; Rila Amalia; Annisa Puspasari (Jurnal Simki Economic, 2024)
This research was conducted on Aqua consumers in Sukajadi District, Bandung City. The aim of this research is to determine the extent to which brand image and brand awareness influence purchasing decisions, either partially or simultaneously. This research uses descriptive and associative methods. The unit of analysis in this research is individuals, namely Aqua consumers in Sukajadi District, Bandung City, with a sample of 97 respondents. The sampling technique is based on certain criteria. The analytical method used is multiple linear regression, as well as testing the validity and reliability of research instruments. The research results show that brand image and brand awareness influence purchasing decisions, both partially and simultaneously. Brand image has an influence of 14.8% on purchasing decisions, while brand awareness has an influence of 22.3%. Overall, brand image and brand awareness have an influence of 37.1% on purchasing decisions.